Metode Menabung Perspektif Zaman Nabi Yusuf As. - Agung Mandiro Cahyono (JOURNAL OF SHARIA ECONOMICS, 2019)
Saving is an activity to prepare future costs so that all the necessities of life remain stable and orderly. Mental preparation before saving is to be frugal. Without this it is very difficult to save. Various methods of saving, including saving at home, saving in the bank. The author examines the method of saving the number of perspectives in the time of the Prophet Joseph (as). that is, setting aside more of the earth's savings than allocating consumptive needs. As a result, when a famine occurs / economic crisis, the savings can meet the conditions of a famine that are met in a stable and orderly manner. Saving for 7 years, the savings can meet the needs for the next 7 years during famine. Writing this with the literature method, which uses the approach of interpretive studies and then analyzed and applied in the present age. The results of the analysis that the theory of saving is a quota of more savings the money from income than expenditure. Keywords: Saving, Age of the Prophet Joseph